Is there an association between nutritional status and intellectual capabilities of adolescents? - Stajic, Dalibor; Popovic, Bojana; Cpajak, Miljan; Ribaric, Senka; Djonovic, Nela (Progress in Nutrition, 2018)
The aim of this study was to investigate the correlations among lifestyles, eating habits, nutritional status and intellectual capabilities of adolescents. A cross-sectional study was carried out using anthropometric measurements and standardized food questionnaire. The sample consisted of 151 adolescents attending a secondary school in central Serbia. Academic achievement was estimated through grade point average (GPA) in the previous academic year. Intellectual capabilities were expressed through intelligence quotient (IQ) determined by Cybernetic battery of intelligence (KOG 3). Totally, 14.5% of students were categorized as overweight or obese. No strong correlation was found between specific dietary habits and nutritional status of adolescents. The percentage of respondents with IQ>110 was higher in the group with increased body mass index (BMI percentile>85) compared to that in the group with normal body weight or underweight (38.5% vs. 15.7%). Besides, 16.7% of students with BMI percentile<85 and only 7.7% of students with BMI percentile>85 had IQ<90. However, Spearman correlation coefficient indicated no strong correlation between IQ test results and students’ BMI (ρ=0.144). On the other hand, students with lower academic performance (GPA<3.5) were more prone to certain dietary habits such as frequent consumptions of coffee (p=0.002) and fast food (p=0.044). On the contrary, sedentary lifestyles were rather typical for adolescents with better academic achievements GPA>3.5 (p=0.009). A significant correlation was found between students’ IQ and height (Spearman’s ρ=0.352). Although there was no strong correlation between intellectual capabilities and nutritional status of adolescents, certain eating habits and lifestyles might be associated with intellectual performance.